Quantitative analysis of auxin metabolites in lychee flowers. Issue 3 (3rd February 2021) - Kim, Ryunhee; Osako, Yutaro; Yamane, Hisayo; Tao, Ryutaro; Miyagawa, Hisashi
ABSTRACT: To investigate the modulation of endogenous indole-3-acetic acid (IAA) level by biosynthesis and inactivation during floral development, IAA and its metabolites were analyzed by LC-ESI/MS/MS in Lychee ( Litchi chinensis Sonn.) flowers. In the bloomed flowers, the level of free IAA was higher in males than in females. In contrast, the total sum level of IAA metabolites was higher in females than in males, suggesting a higher biosynthetic activity of IAA in the females before the bloom. A detailed time-course analysis from the bud stage to the developing flower stage showed higher levels of IAA in females than males. The major metabolites were oxidized IAA in both sexes. The results suggest that IAA is involved in the maturation of female floral tissues in lychee, and oxidative metabolism plays an essential role in controlling the free IAA levels therein. Graphical Abstract: